Organizational crime in Brazil: the Petrobras case - Valarini, Elizângela (Organizational crime, 2023)
Since March 2014, one of Brazil’s most important companies, Petrobras, has become the main protagonist of the biggest corruption scandal in Brazil, revealed by Car Wash Operation. The corrupt scheme had not only a massive impact on the companies’ economic performance but also a huge effect on Brazilian politics, changing the political landscape. The scandal showed not only the informal side of the Brazilian economic and political interaction but brought to light the dark side of the Brazilian system of political financing and business rules. Involved in the corruption scheme were essentially members of the economic and political elites: owners and top executives of the largest Brazilian construction companies, senior executives of Petrobras, and politicians from some of the most important Brazilian political parties. Adopting a sociological perspective on corporate crime and corruption, this chapter aims to examine how mechanisms on the side of private corporations, combined with environmental factors in which companies are imbedded, contribute to political corruption. The analysis focuses on Brazilian private companies charged in Operation Car Wash by using court records produced by the Federal Court of Curitiba.